A Survey of Internet of Things Services Provision by Telecom Operators - Manal Alareqi (EAI Endorsed Transactions on Internet of Things, 2018)
Telecom industry will play a vital role in delivering Internet of Things (IoT) solutions and services. Researchers trust that IoT services deployment by Telecom is inevitable during the next few years. Nowadays, digital development overgrows, thus Telecom operators should consider IoT as the next evolution in their business plans. If an operator’s services confined to traditional services such as calling, they will lose a lot of added values and opportunities. In the end, they will find themselves out of the competition. Recently, the research community has addressed this topic and enriched it by highlighting related issues to help operators and researchers to move forward in this field. This paper presents a sound review for this topic covering the most significant related issues such as success elements, strategies and Low-Power Wide-Area (LPWA) standards provided by Telecom operators for IoT provision.